Modelling the Irish economy: a progress report on the Central Bank's macroeconometric model - Central Bank of Ireland, Research Department (Statistical and Social Inquiry Society of Ireland, 1979)
Methods of empirical economic analysis have undergone enormous changes in recent decades. The availability of improved statistics and of high-speed computers have facilitated this process, but the increasing ambition and complexity of economic policy itself have perhaps been the major stimuli. In most of the economically advanced countries and, increasingly, in developing countries also, analysis of macroeconomic policy options is carried out with the aid of large-scale econometric models. Such models are systems of simultaneous equations, hundreds of them in the larger models, designed to encapsulate the interrelationships of the main economic variables. The models, in principle anyway, will predict the impact of changes in policy, say in tax rates, on variables like the levels of output and employment.
Read before the Society, 2 November 1978
Keywords: Macroeconometric model of Irish economy; Central Bank of Ireland; Macroeconomic forecasting; Large scale econometric models; 314.15